Analisis Kepuasan Bermain Roblox di Indonesia Menggunakan Metode SERVQUAL - radityaarkhana; Emy L. Tahuhey (CV Edujavare Publishing, 2025)
The growth of the online gaming industry in Indonesia continues to show a positive trend, especially on popular platforms like Roblox. This study aims to analyze the satisfaction level of playing Roblox in Indonesia using the SERVQUAL method, which measures the gap between players' expectations and perceptions on five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data were collected through online questionnaires from 30 active Roblox users and analyzed using SPSS for validity, reliability, and GAP (P–E) analysis. The results indicate a negative average GAP in some dimensions, suggesting that players' perceptions do not fully meet their expectations. This study provides recommendations for Roblox developers to improve service quality and enhance player satisfaction.